Pengaruh Panjang Sambungan Pada Beton Prategang Segmental Bertulangan Limbah Ban - Maryoto, Agus - (Semarang State University, 2017)
Prestressed concrete with reinforcement of waste tires can improve significantly the flexural strength. The problems when applied in the project is difficult to move from the production site to the location of the structure. One method to overcome this is applied precast segmental. Molded concrete blocks with a shorter length is easy to carry to the project site. Connectors between concrete beams segment plays a very important thing. This study tried to determine the influence of length of connectors on the precast segmental concrete. Three specimens are concrete beam with no connections, segmental concrete blocks with a connection length of 10 cm and 15 used in the experiment. Flexural testing was conducted to determine the carrying capacity of the three beams. The result showed that the length of the connection contribute on flexural strength of concrete beam. However, segmental concrete beam flexural capacity was still below the concrete beam flexural capacity without connection.Â Beton prategang bertulangan limbah ban dapat meningkatkan kuat lentur yang cukup besar. Kendalanya ketika diaplikasikan di lapangan adalah kesulitan memindahkan dari tempat pengecoran ke lokasi struktur. Salah satu metode untuk mengatasi ini digunakanlah pracetak segmental. Balok beton dicetak dengan ukuran panjang yang pendek sehingga mudah dibawa ke lokasi proyek. Penyambung antara segmen balok beton memegang peranan yang sangat penting. Studi ini mencoba mengetahui pengaruh panjang sambungan pada jenis sambungan yang sudah tertentu. Tiga buah benda uji yaitu balok beton tanpa sambungan, balok beton segmental dengan panjang sambungan 10 cm dan 15 digunakan dalam eksperimen. Pengujian lentur dilakukan untuk mengetahui kapasitas dukung ketiga balok tersebut. Hasilnya menunjukkan bahwa panjang sambungan berpengaruh terhadap kuat lentur balok beton segemental. Namun kapasistas lentur balok beton segmental masih dibawah kapasitas lentur balok beton tanpa sambungan.Â